1997
DOI: 10.2186/jjps.41.130
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weight Change of Maxillary Complete Denture on Masticatory Movement.

Abstract: This study was conducted to investigate the effect of weight change of upper complete denture on masticatory function in case of five maxillary edentulous patients who had adequate retention and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Because of its low density, titanium dentures are more lightweight than conventional metal‐base dentures. It was reported that the difference in the weight of well‐fitting maxillary and mandibular titanium complete dentures did not affect jaw movements, denture stability or patient preference compared with conventional dentures (69, 70). However, the patients’ preferences were likely to be influenced by the preconceived idea that a heavy denture contributes to mandibular denture stability and that light maxillary dentures are hard to remove.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its low density, titanium dentures are more lightweight than conventional metal‐base dentures. It was reported that the difference in the weight of well‐fitting maxillary and mandibular titanium complete dentures did not affect jaw movements, denture stability or patient preference compared with conventional dentures (69, 70). However, the patients’ preferences were likely to be influenced by the preconceived idea that a heavy denture contributes to mandibular denture stability and that light maxillary dentures are hard to remove.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patients’ preferences were likely to be influenced by the preconceived idea that a heavy denture contributes to mandibular denture stability and that light maxillary dentures are hard to remove. Thus, titanium maxillary dentures may be preferred by the patients who have such preconceived ideas (69). On the other hand, facial prostheses should be fabricated as light as possible because they cannot be given enough retention (71).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, titanium would be suitable for use in large RPD frameworks. Especially, some patients prefer light maxillary dentures because they believe that lightweight dentures will be more comfortable 62) . These patients prefer titanium dentures for the maxillary jaw.…”
Section: Lightweightmentioning
confidence: 99%
“…The test food used was one piece of fresh gummy candy ¶ (approximately 4 gm). All chewing was performed on the side preferred by each patient and proceeded at the patient's own pace until swallowing (24)(25)(26)(27). This process was repeated three times per denture.…”
Section: Measurement Of Masticatory Movementsmentioning
confidence: 99%
“…TI‐retained overdentures were fabricated by converting the existing mandibular complete dentures of seven mandibular edentulous patients. To observe the stability of the TI‐stabilized overdentures (24–28), masticatory movements (mandibular movements during chewing) were measured before and after TI placement, and the patients were questioned about the function of each denture.…”
Section: Introductionmentioning
confidence: 99%